Development of interactive multimedia based on educational games of plant parts and their functions to improve student learning outcomes - None Nur Fadila; Karimatus Saidah; Dhian Dwi Nur Wendha (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Natural Science (IPA) is an activity to study nature systematically through actual activities and trains students to think critically and objectively to achieve learning objectives. Using learning media in the learning process can support success in the learning process. This study aims to determine interactive multimedia development's validity, practicality, and effectiveness based on the educational game